Fecundity Of Blue Swimming Crab, Portunus Pelagicus Linnaeus, 1758 From Sematan Fishing District, Sarawak Coastal Water Of South China Sea - Ikhwanuddin, Abdullah @ Polity; Juariah Hafsya, Muhamad; Shabdin, Mohd Long; Abol-Munafi, Ambok Bolong (Universiti Malaysia Sarawak (UNIMAS), 2011)
A total of 57 pieces of ovigerous females were sampled through the study period of 14 months from the commercial catches that were made at the Sematan Fishing District, Sarawak coastal water. These ovigerous females were used to determine the crab fecundity through mean number of egg per crab. The present study shows that the mean number of egg is 2,132,924 with mean egg size (volume) 9.3×10-6 ml and mean egg size (diameter) 383.6 μm measured using volumetric sub sampling. Fecundity was significantly related to crab size with larger crabs producing a greater number of eggs through linear regression of the fecundity – carapace width relationship. The fecundity-carapace width relationship for P. pelagicus was estimated as follows; y = 106804x + 375319 (R2=0.0229; n=57). The study shows that the egg size is significantly larger (P < 0.05) as the eggs nearly about to hatch which is black in colour.